Developing a Novel Two‐Dimensional Culture System to Enrich Human Prostate Luminal Progenitors that Can Function as a Cell of Origin for Prostate Cancer. (29th September 2016) - Zhang, Dingxiao; Lin, Kevin; Lu, Yue; Rycaj, Kiera; Zhong, Yi; Chao, Hsueh‐Ping; Calhoun‐Davis, Tammy; Shen, Jianjun; Tang, Dean G.
Abstract: Elucidating the cell of origin of cancer has great significance in stratifying patients into appropriate treatment groups and for developing novel targeted therapies. Early studies demonstrate that only stem‐like basal cells in the normal human prostate (NHP) can function as the cell of origin for prostate cancer (PCa). Here, we show that the organoids derived from bulk NHP luminal cells can also be tumorigenically transformed. We further show that the WIT medium, which is used to culture human mammary epithelial progenitor cells, when combined with the ROCK inhibitor, can readily propagate a population of progenitor‐like cells from the primary NHP luminal cell isolates. Such functionally defined luminal progenitors can be transformed by distinct sets of genetic perturbations (i.e., AR+AKT/ERG or c‐MYC+PTEN knockout) to form tumor glands. Genome‐wide RNA‐Seq analysis of freshly purified unperturbed human benign prostatic basal and luminal cells and culture‐expanded lineage‐specific stem/progenitor populations reveals that the luminal progenitors possess a distinct gene expression profile that is greatly enriched in advanced, castration‐resistant, and metastatic PCa, and it associates with poor patient survival. The ability of the simple two‐dimensional culture system reported herein to greatly enrich NHP progenitor‐like cells should facilitate biological and biochemical studies as well as high‐throughput screening in these cells and in progenitor‐like PCa cells. Stem Cells Translational Medicine 2017;6:748–760